HAK-HAK ANAK DALAM PERSPEKTIF HUKUM ISLAM - Sri Mulyani (STIS Nahdlatul Ulama Aceh, 2021)
In the view of Islam, the rights of the child are very important to pay attention to, because seeing Islam as a perfect religion and rahmatal lil'alamin, of course there is a clear description of this very important issue. Islam has paid great attention to children's rights. The rights of children in Islam include the right to care for religion, the right to care for offspring, the right to health care, the right to care for reason and socio-economic rights.